2014
DOI: 10.1177/1533317514545615
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, Sedentary Pastimes, and Cognitive Performance in Healthy Older Adults

Abstract: Background Moderately vigorous physical activity (MVPA) provides a protective affect against cognitive decline and cardiovascular risk factors. Less is known about sedentary pastimes or non exercise physical activity (NEPA) and cognitive performance. Method 125 healthy adults 65 or older with no clinical evidence of cognitive impairment were enrolled. The CogState computerized neurocognitive battery was administered. Leisure activities were measured using the Community Health Activity Program for Seniors (CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 43 publications
1
49
0
6
Order By: Relevance
“…Two studies24 25 used the Modifiable Activity Questionnaire (MAQ) to assess sedentary behaviour,32 a single study29 used the Community Health Activities Model Program for Seniors (CHAMPS) questionnaire,42 another study28 used the Sedentary Behaviour Questionnaire (SBQ)39 and the last study30 used an unnamed questionnaire developed from previous investigations to assess sedentary time 44. Each of the four questionnaires showed evidence of validity and reliability; however, only the CHAMPS, MAQ and SBQ were previously validated against a criterion measure 39 47 50…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies24 25 used the Modifiable Activity Questionnaire (MAQ) to assess sedentary behaviour,32 a single study29 used the Community Health Activities Model Program for Seniors (CHAMPS) questionnaire,42 another study28 used the Sedentary Behaviour Questionnaire (SBQ)39 and the last study30 used an unnamed questionnaire developed from previous investigations to assess sedentary time 44. Each of the four questionnaires showed evidence of validity and reliability; however, only the CHAMPS, MAQ and SBQ were previously validated against a criterion measure 39 47 50…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen different measures of cognitive function were used across the eight studies 23–30. Studies examined the following areas of cognition: (1) five measured memory;23 24 29 30 (2) five measured executive function;23–25 28 30 (3) four measured processing speed;23 28–30 (4) two measured incidence of cognitive impairment or all-cause dementia26 27 and (5) one measured perceptual organisation and planning 30. Three studies created scores for global cognitive function 23 29 30…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that participation in engaging leisure activities could increase cognitive reserve, thus delaying loss of cognitive function 51. Conversely, one study found that greater frequency of socially or cognitively engaging pastimes was associated with lower executive function,62 although TV time was included as one of the sedentary pastimes which may be influencing those results. Clearly, more research is needed to determine if different sedentary behaviours have differential effects on cognitive function.…”
Section: Methodsmentioning
confidence: 99%
“…Sedentary behavior in the elderly population has been related to cognitive deficits, which may in turn impair the well-being and quality of life of such individuals, while physical exercise plays an important role in mitigating or even protecting against such deleterious effects of aging 26,27 . Evidence shows that sedentary elderly persons have a worse quality of life than active individuals 28 .…”
Section: Discussionmentioning
confidence: 99%